PROFIL WILAYAH DESA CIBINUANG DAN DESA SAKERTA TIMUR SEBAGAI DAERAH RESAPAN AIR SUNGAI CISANGGARUNG - Rachmat, Nurhaliza Ainur; Kiat, Zidan Hidsa; Antika, Sely; Ramadhani, Disa Banua Dwi; Damayanti, Fitri Dwi; Sari, Desy Permata; Priatama, Aldi (Fakultas Kehutanan dan Lingkungan, Universitas Kuningan, 2024)
Village management in water catchment areas is an important task to maintain environmental health and manage natural resources. Water catchment areas or catchment areas are areas used for water capture, water storage and water distribution. Increasing population and increasing living needs can cause changes in land use, such as converting land from open areas to built-up areas. Apart from that, converting land from open areas to built-up areas can also reduce water catchment areas. This research aims to determine the potential of Cibinuang Village and East Sakerta Village to become tourist villages in Kuningan Regency. Apart from that, it is also to find out what obstacles are faced in developing Cibinuang Village and East Sakerta Village, Kuningan Regency.The method used in this research is a qualitative method, the types of qualitative methods used to obtain written and oral data regarding the regional profile of Cibinuang Village and East Sakerta Village as the Cisanggarung River Water Catchment Area include historical, descriptive, case study and experiment. The data collection technique used was an in-depth interview technique using interview guidelines, observation and the use of documentary materials.Keywords: Catchment area, catchment, conservation, qualitative, historical, descriptive, case study, experiment, interview, observation.